Mary Augusta Ward's "perfect economist" and the logic of anti-suffragism - Coit, E (Johns Hopkins University Press, 2015)
This article exposes the engagement of Mary Augusta Ward's Marcella (1894) with the emergent academic discipline of economics, drawing connections between Ward's influential novel and texts by the economic thinkers John Ruskin, Beatrice Webb, and Alfred Marshall. Marcella, I contend, represents gendered forms of economic knowledge, and this representation expresses the often misunderstood "difference feminism" that informs both Ward's anti-suffrage stance and her advocacy for women's education. Bringing together historical scholarship on the professionalization of economics and literary scholarship on nineteenth-century feminisms, this reading of Ward's novel proposes that economic learning plays an important role in the thinking that shapes the British anti-suffrage movement.